Effect of organic solvents on the growth of TiO2 nanotubes: An insight into photocatalytic degradation and adsorption studies - Zulfiqar, M. (Elsevier Ltd, 2020)
Alcohols or solvents have attained much attraction in scientific community to regulate the shape and surface characteristics of TiO2 for multiple applications. Herein, single-walled TiO2 nanotubes (SWTNTs) were synthesized via the simple hydrothermal method in presence of different organic solvents, namely 1-propanol and 2-propanol under alkaline environment. The physicochemical properties of the as-developed SWTNTs were scrutinized using XRD, TEM, FESEM, BET and DRS. The growth of SWTNTs via 1-propanol resulted in a remarkable enhancement in the performance up to 94.97 of Acid orange 7 (AO7) was degraded. The outstanding photodegradation performance observed was attributed to the better morphological structure and crystallinity, evidently from the structure and microscopic image analysis. The enhanced light absorption capacity towards the visible light region significantly improved the photodegradation performance of the as-developed SWTNTs. The photodegradation rate of AO7 on SWTNTs was well explained via the modified Langmuir-Hinshelwood kinetic model. Furthermore, adsorption kinetic and isotherm analysis revealed that as-developed SWTNTs obeyed the pseudo-first-order kinetics and Langmuir isotherms. Congruently, the values of thermodynamic parameters, and activation energy revealed that the adsorption of AO7 is endothermic, spontaneous and chemisorption in nature. The rise in temperature was found to be more feasible for increased removal of AO7. This enhanced degradation activities of solvent-controlled SWTNTs was strongly associated with the well-defined morphology, larger specific surface area as well as smallest band gap energy values. This research offered a new direction for the growth of catalysts with excellent and stable photodegradation and adsorption activities in the purification of organic wastewaters. Â© 2020 Elsevier Ltd